(untitled) (Communications in Mathematical Research, 2021)
Let R be a 2-torsion free prime ring and L a noncommutative Lie ideal of R. Suppose that (d, σ) is a skew derivation of R such that x^s d(x)x^t = 0 for all x ∈ L, where s, t are fixed non-negative integers. Then d = 0.